Proposed basic word list in Pilipino for Waray-speaking grade one learners - Acidre, Soledad Balintong 1941- (s.n.], 1974)
This study is concerned with evolving a basic word list in Pilipino for Waray-speaking grade one learners utilizing two main sources of data: (1) the reading vocabulary gathered from five basic Filipino readers most commonly used by the grade one teachers of Tacloban District IV, and (2) the speaking vocabulary collected from the responses and utterances of 320 grade one pupils in Tacloban District IV during their formal classroom recitations in Pilipino.